Rabbit trap [videorecording (DVD)] - Chainey, Bryn; Patel, Dev, 1990-; McEwen, Rosy; Croot, Jade (Magnolia Home Entertainment, 2025)
Married couple Daphne and Darcy Davenport are two musicians who moved from London to a cottage in Wales to complete their new album. By accident they record a mystical sound never heard before and gradually disconnect from reality.